2015
DOI: 10.1002/2014jc010466
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the surface salinity signature of Gulf Stream cold‐core rings in Aquarius synergistic products

Abstract: New sea surface salinity (SSS) observations derived from satellite remote sensing platforms provide a comprehensive view of salt exchanges across boundary currents such as the Gulf Stream. The high resolution (45 km spatial resolution and 3 day repeat subcycle) of the Soil Moisture and Ocean Salinity (SMOS) observations allows detection (and tracking) of meander and ring structures of the Gulf Stream from SSS maps. These structures are, however, not resolved by the relatively lower resolution (100 km and 7 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Resent state of the art satellite observations of SSS, by NASA's Aquarius/SAC‐D satellite [ Lagerloef et al ., ] and ESA's Soil Moisture and Ocean Salinity (SMOS) satellite [ Kerr et al ., ], present an opportunity to complement the existing satellite observations of SST, surface winds, air‐sea fluxes, and other variables, to observe the signature of mesoscale eddies. The potential of new satellite measurements to observe mesoscale features and eddies have been demonstrated in a few recent studies [ Reul et al ., ; Umbert et al ., ; Isern‐Fontanet et al ., ]. Yet extracting such information from medium‐resolution and noisy satellite data requires application of selective data analysis tools.…”
Section: Introductionmentioning
confidence: 99%
“…Resent state of the art satellite observations of SSS, by NASA's Aquarius/SAC‐D satellite [ Lagerloef et al ., ] and ESA's Soil Moisture and Ocean Salinity (SMOS) satellite [ Kerr et al ., ], present an opportunity to complement the existing satellite observations of SST, surface winds, air‐sea fluxes, and other variables, to observe the signature of mesoscale eddies. The potential of new satellite measurements to observe mesoscale features and eddies have been demonstrated in a few recent studies [ Reul et al ., ; Umbert et al ., ; Isern‐Fontanet et al ., ]. Yet extracting such information from medium‐resolution and noisy satellite data requires application of selective data analysis tools.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the potential of new satellite measurements of SSS to describe features not well captured by SST maps such as fresh‐core Gulf String rings [ Reul et al , ; Umbert et al , ]. However, eddies in the Algerian Basin are more difficult to detect by SMOS because they are attached to the coast or located at distances from coast were the contamination from land in the L band microwave is important [ Font et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…SMOS SSS maps are well correlated with in situ measurements although the former has a smaller dynamical range. Despite this limitation, SMOS SSS maps capture the key dynamics of Algerian eddies allowing to retrieve velocities from SSS with the correct sign of vorticity.Recent studies have demonstrated the potential of new satellite measurements of SSS to describe features not well captured by SST maps such as fresh-core Gulf String rings [Reul et al, 2014;Umbert et al, 2015]. However, eddies in the Algerian Basin are more difficult to detect by SMOS because they are attached to the coast or located at distances from coast were the contamination from land in the L band microwave is important…”
mentioning
confidence: 99%
“…While there have been notable efforts to improve the quality of retrievals [5], [6], L-band radiometry is still in its infancy, and the quality of derived salinity products is expected to improve with time. Currently, higher-level processing efforts, i.e., various spatial and temporal averaging and data fusion techniques, have been implemented to better recover structured and meaningful geophysical information from remote sensing SSS retrievals [7], [8], [9].…”
Section: Introductionmentioning
confidence: 99%